Cointegration and the joint confirmation hypothesis - Gabriel, Vasco J. (2003)
In this paper, the discussion concerning the joint use of unit root and stationarity tests is extended to the case of cointegration. Critical values for testing the joint confirmation hypothesis of no cointegration are computed and a small Monte Carlo experiment evaluates the relative performance of this approach.